2008
DOI: 10.1080/02699930801886706
|View full text |Cite
|
Sign up to set email alerts
|

Parental rearing as a function of parent's own, partner's, and child's anxiety status: Fathers make the difference

Abstract: Parents of children with anxiety disorders are found to be over controlling and more rejecting in parentÁchild interactions than parents of control children. However, most studies included mothers, and the rearing behaviour of fathers of anxious children is largely unknown. Also, it remains unclear whether parents' control and rejection is a response to child's anxiety, or (also) results from parents' own anxiety. Participants were 121 children referred with anxiety disorders and 38 control children, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 26 publications
1
44
1
Order By: Relevance
“…These findings are somewhat surprising considering the recent literature highlighting the unique contribution of fathers on child anxiety (for review : Bögels & Phares, 2008) and the suggestions that anxious fathers may be less effective in their role of autonomy and encouragement, resulting in increased child anxiety (Bögels, Bamelis, & van der Bruggen, 2008). Instead, our results (although the effect was small) suggest that increased negative affectivity in fathers does not directly predict the development of child anxiety.…”
Section: Discussioncontrasting
confidence: 96%
“…These findings are somewhat surprising considering the recent literature highlighting the unique contribution of fathers on child anxiety (for review : Bögels & Phares, 2008) and the suggestions that anxious fathers may be less effective in their role of autonomy and encouragement, resulting in increased child anxiety (Bögels, Bamelis, & van der Bruggen, 2008). Instead, our results (although the effect was small) suggest that increased negative affectivity in fathers does not directly predict the development of child anxiety.…”
Section: Discussioncontrasting
confidence: 96%
“…The parenting and family functioning constructs that are measured by the RBQ and FFS are therefore not explicitly targeted in the CCBT. The program encompasses psycho education, challenging anxiety-provoking thoughts, coping behavior, exposure in vivo according to a fear hierarchy and a reinforcement system, (behavioral) experiments, and relapse prevention (Bodden et al 2008;Bögels et al 2008). Research showed that 73 % of the children recovered from their primary anxiety diagnosis 3 months after CCBT (Bodden et al 2008).…”
Section: Treatmentsmentioning
confidence: 99%
“…Thus, it may be prudent for future studies to examine these processes in clinical samples. It is also important to note that the examination of these processes in fathers is imperative (e.g., Bogels et al 2008), as is the consideration of how child characteristics interact with parental traits to shape family interactions and relationships (e.g., Schrock and Woodruff-Borden 2010).…”
Section: Discussionmentioning
confidence: 99%